The Effectiveness of Flashcard Media in Enhancing Science Learning Outcomes among Elementary School Students - Puri Anjar Wati; Yasinta Mahendra (Universitas Pendidikan Ganesha, 2025)
Natural Science (IPA) education in elementary schools continues to face challenges, particularly the low academic achievement of students in understanding and retaining scientific concepts. This study aims to explore the impact of flashcard use on elementary students' science learning outcomes. The research adopts a Systematic Literature Review (SLR) method. The subjects of this study include elementary school students from various previously conducted studies. Data were collected through the analysis of documents and scholarly articles discussing the effectiveness of flashcards in learning. Data analysis was carried out using a qualitative descriptive approach to identify patterns of findings from different sources. The results indicate that the use of flashcards, both digital and conventional, significantly improves students’ conceptual understanding and learning outcomes. The implementation of this media encouraged more students to reach or even exceed the Minimum Competency Criteria (KKM). Beyond its positive impact on academic performance, flashcards also prove effective in supporting both individual and group learning, enhancing vocabulary acquisition, and creating a more interactive and enjoyable learning experience. Based on these findings, the study confirms that flashcards are an effective instructional tool for improving the quality of science education in elementary schools. The implication is that the integration of flashcards into teaching strategies should be considered as an innovative effort to strengthen science education at the elementary level.